2002
DOI: 10.1289/ehp.02110s61085
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of p-nitrophenol in the urine of residents whose homes were contaminated with methyl parathion.

Abstract: We thank all the state and local health officials involved with sample collections and shipments. Throughout the period of laboratory-based measurements, many people provided invaluable assistance in biomonitoring that contributed to the rapid turnaround of data. We thank D. Methyl ParathionDuring the last several years, illegal commercial application of methyl parathion (MP) in domestic settings in several U.S. Southeastern and Midwestern States has affected largely innercity residents. As part of a multiage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…PNP may undergo conjugation with other molecules (Barr et al, 2002). The conjugation reactions are catalyzed by enzymes and are common in biotransformation processes of xenobiotics, usually promoting binding of toxic compounds slightly polar to more polar molecules, facilitating the excretion of the compound (Costa et al, 2004).…”
Section: Strainsmentioning
confidence: 99%
“…PNP may undergo conjugation with other molecules (Barr et al, 2002). The conjugation reactions are catalyzed by enzymes and are common in biotransformation processes of xenobiotics, usually promoting binding of toxic compounds slightly polar to more polar molecules, facilitating the excretion of the compound (Costa et al, 2004).…”
Section: Strainsmentioning
confidence: 99%
“…LODs have been reported that range from 0.05 to 2 ng/mL for the major urinary metabolites of chlorpyrifos and parathion [3, 11,12] and from 0.5 to 1 ng/mL for the major metabolite of diazinon [13]. Several high-performance liquid chromatography (HPLC) tandem mass spectrometry (MS/MS) methods for the measurement of OP metabolites in urine also has been published [4,6,13,14,15]. HPLC-MS/MS analysis, using atmospheric pressure chemical ionization (APCI), of specific metabolites of diazinon and malathion have been reported, with LODs <0.5 ng/mL [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of potential human exposure to this pesticide led ODH to formally request technical assistance from the Centers for Disease Control and Prevention (CDC). This article describes the initial investigation in Ohio and supports the importance of using both biological markers of exposure (1,2) and environmental markers of contamination (3) when making public health decisions about the cleanup of methyl parathion-sprayed homes.…”
mentioning
confidence: 79%